Modeling Nearby Low-Luminosity Active-Galactic-Nucleus Jet Images at All VLBI Scales - Hung-Yi Pu; Keiichi Asada; Masanori Nakamura (Galaxies, 2022)
Relativistic jets from nearby low-luminosity active-galactic-nuclei (LLAGN) were observed by Very-Long Baseline Interferometry (VLBI) across many orders of magnitude in space, from milliparsec to sub-parsec scales, and from the jet base in the vicinity of black holes to the jet collimation and acceleration regions. With the improved resolution for VLBI observations, resolved VLBI jet morphologies provide valuable opportunities for testing and constraining black hole jet physics. In this review, we summarize and discuss the current progress of modeling nearby LLAGN jet images from horizon scales to large scales, including the construction of jet models and the assumed emission details. Illustrative examples for jet image modeling are also given to demonstrate how jet image features may vary with the underlying physics.